Learning the Values of Religious Moderation in the Context of Higher Education - Andrianto Andrianto; Sutrisno Sutrisno; Muqowim Muqowim (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
Indonesia, as a country with religious and cultural diversity, needs education that teaches moderate and tolerant attitudes, especially in higher education. Yogyakarta State University (UNY) has an important role in instilling religious moderation values to its students to encourage harmony in a plural society. This research aims to explore the implementation of religious moderation values education at UNY and analyse the application of such learning in the context of higher education. The approach used is qualitative with a case study method, where data is collected through in-depth interviews with students, lecturers, and managers of religious education programmes, as well as observations of activities related to religious moderation. The data obtained included interviews with relevant parties, as well as observations of religious education programs at UNY, such as religious education courses, interfaith dialogue forums, and student organisation activities. The results show that UNY has successfully integrated the values of religious moderation through various educational programmes and activities on campus. However, challenges such as differences in religious understanding, the influence of radicalisation from outside the campus, and limited facilities for wider dialogue are still obstacles in this effort.